The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1103/physreva.94.023608
|View full text |Cite
|
Sign up to set email alerts
|

Coarsening and thermalization properties of a quenched ferromagnetic spin-1 condensate

Abstract: We examine the dynamics of a quasi-two-dimensional spin-1 condensate in which the quadratic Zeeman energy q is suddenly quenched to a value where the system has a ferromagnetic ground state. There are two distinct types of ferromagnetic phases, i.e. a range of q values where the magnetization prefers to be in the direction of the external field (easy-axis), and a range of q values where it prefers to be transverse to the field (easy-plane). We study the quench dynamics for a variety of q values and show that t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 66 publications
(125 reference statements)
3
50
0
Order By: Relevance
“…Universal scaling with exponent β 1/2 has recently been observed experimentally in a ferromagnetic spin-1 Bose gas in a near-1D geometry [10]. Theoretical studies have shown that universal scaling can occur in the ordering process of one-and quasi twodimensional (quasi-2D) spin-1 as well as binary Bose gases after a parameter quench into an ordered phase [11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Universal scaling with exponent β 1/2 has recently been observed experimentally in a ferromagnetic spin-1 Bose gas in a near-1D geometry [10]. Theoretical studies have shown that universal scaling can occur in the ordering process of one-and quasi twodimensional (quasi-2D) spin-1 as well as binary Bose gases after a parameter quench into an ordered phase [11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The two-body problem [11] is an example but the separation can also be done for larger number of particles [12][13][14]26,27] at the cost of using more sophisticated methods of describing the relative motion [15,22]. In practice, the mentioned transformation of variables is difficult to perform straightforwardly, however it is a standard tool in a theoretical analysis of few-body problems [30][31][32]. In the following we will separate the the centre-of-mass motion within the scope of the second quantisation formalizm.…”
Section: The Centre-of-mass Framementioning
confidence: 99%
“…Simulations are performed using the spin-1 GPE with weak noise (representing the vacuum fluctuations) added to seed the dynamic instabilities. The noise is added to the polar condensate state as described in [39] and then the spin rotations described in the previous subsection are applied to this state to prepare the initial condition. The simulation is performed on a 2D square grid of spatial dimension L×L covered by a grid of N N L Ĺ equally spaced points, with periodic boundary conditions.…”
Section: Simulationsmentioning
confidence: 99%
“…( ) [21,39]. In this regime the system should exhibit the phenomenon of 'phase-ordering percolation' [27], whereby the effective size of the system diminishes in time as L l t d ( ).…”
Section: Outlook and Conclusionmentioning
confidence: 99%